RELATIONSHIP BETWEEN OVIPOSITION OF Podocnemis unifilis AND WATER LEVEL IN PERUVIAN AMAZONIAN FLOODPLAINS - Véliz Rosas, Claudia (2022)
In the Amazon floodplains, hydrological variability plays a crucial role by shaping the habitat, offering shelter and feeding or breeding areas. During the dry season, some fresh water turtles such as the yellow-spotted turtle (Podocnemis unifilis Troschel, 1848) use the sand banks at point bar areas as breeding sites, which must be available in time for the start of oviposition. In this study, we used altimetry-derived water level data from radar satellites combined with in-situ hydrological measurements to evaluate water level variations and relate them to oviposition starting dates (2003-2012) from Pacaya-Samiria National Reserve, Peru. Synchronous hydrological behavior was found between the major river stems (Ucayali and Marañon) and the inner rivers (Pacaya and Samiria), thus enabling the utilization of water level in the main river stem to correlate with oviposition in the inner rivers. Mean oviposition date was July 23nd with selection of a narrow water level range (92 masl ± 0.9 SD). Consistent shifts towards early/late oviposition were found for years with early/late dry season onset. Extreme biological shifts in terms of oviposition date onset, were identified for specific years (2004, 2010 and 2011) mainly for the extreme dry year of 2010.